2022
DOI: 10.1002/ecy.3665
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of light use favors a plant invader in nitrogen‐enriched ecosystems

Abstract: Eutrophication is believed to promote plant invasion, resulting in high growth performances of invasive plants and, therefore, the great potential for growthinduced intraspecific competition for light. Current hypotheses predict how eutrophication promotes plant invasion but fail to explain how great invasiveness is maintained under eutrophic conditions. In diverse native communities, co-occurring plants of varying sizes can avoid light competition by exploiting light complementarily; however, whether this mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In China, eutrophication will likely continue to increase, and is likely to aggravate the invasion of S. alterniflora . In a long‐term field experiment ( Spartina Invasion and Nitrogen Enrichment [SINE] experiment) in the Yangtze estuary, one of the most eutrophic estuaries in China, researchers from Fudan University found that the light use plasticity of S. alterniflora was enhanced under N enrichment, which facilitated the coexistence of conspecifics of varying sizes, thereby increasing growth and invasiveness of S. alterniflora by alleviating intraspecific competition (Xu, Zhou, et al, 2022). In addition, the negative effects of herbivory under ambient N were shifted to positive effects under N enrichment, with herbivory stimulating complementary increases in density and aboveground biomass (Xu, Zhang, et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…In China, eutrophication will likely continue to increase, and is likely to aggravate the invasion of S. alterniflora . In a long‐term field experiment ( Spartina Invasion and Nitrogen Enrichment [SINE] experiment) in the Yangtze estuary, one of the most eutrophic estuaries in China, researchers from Fudan University found that the light use plasticity of S. alterniflora was enhanced under N enrichment, which facilitated the coexistence of conspecifics of varying sizes, thereby increasing growth and invasiveness of S. alterniflora by alleviating intraspecific competition (Xu, Zhou, et al, 2022). In addition, the negative effects of herbivory under ambient N were shifted to positive effects under N enrichment, with herbivory stimulating complementary increases in density and aboveground biomass (Xu, Zhang, et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…In particular, the complementary effect was rooted in the idea that a more diverse community will have less niches available for invaders (Elton, 1958; Tilman, 2004), but it also means that the niche overlap between invaders and native species in receptive communities would increase with plant species diversity. The higher niche overlap under N enrichment may aggravate competition that favours invaders over native species because invaders always have a high growth rate and phenotypic plasticity, and thus a higher ability to compete for light (Gioria & Osborne, 2014; Liu et al, 2017; Xu et al, 2022; but also see Funk and Vitousek (2007) for the contrary examples of invading in low resource environment). In short, the increased difference in fitness, or the increased competitive advantage of invaders, under N enrichment and the decreased niche difference by higher diversity would together promote competitive exclusion of natives by invaders, and thus eliminate biodiversity resistance (Chesson, 2000; Godoy, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…First, functional traits can reflect the strategies for acquiring nutrients and the competitive advantages of plants. For example, large specific leaf area (SLA) and high plant height always confer fast growth and high competitiveness for light (Liu et al, 2016; Wilson et al, 1999; Xu et al, 2022). Second, functional traits could also reflect the niche difference between species or the niche complementary of a native community (Cadotte, 2017; McGill et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some IEPs have captured the attention of ecologists because of their formation of expanded populations in low diversity stands ( Levine et al., 2003 ; Vilà et al., 2011 ). IEPs may have a competitive advantage over native resident species for the exploitation of nutrients ( Huenneke et al., 1990 ; Davis et al., 2000 ) or light ( Xu et al., 2022 ) that natives are not able to tap ( Sun et al., 2014 ). IEPs with different life forms from the native flora may alter the community structure and habitat heterogeneity of the invaded area, thereby changing the resources available to resident species ( Jager et al., 2009 ; Molinari and D’Antonio, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…In different native communities, symbiotic plants of different sizes can avoid light competition by using light at different spatial or temporal scales, thus maximizing light resource utilization ( Zuppinger-Dingley et al., 2014 ). However, it is unclear whether this mechanism applies to IEPs, especially in the case of nutrient enrichment and the competition for light between IEPs and native species of different life forms ( Molinari and D’Antonio, 2014 ; Xu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%